Endovascular WEB Flow Disruption in Middle Cerebral Artery Aneurysms: Preliminary Feasibility, Clinical, and Anatomical Results in a Multicenter Study - Pierot, Laurent; Klisch, Joachim; Cognard, Christophe; Szikora, Istvan; Mine, Benjamin; Kadziolka, Krzysztof; Sychra, Vojtech; Gubucz, Istvan; Januel, Anne-Christine; Lubicz, Boris (Neurosurgery, 2013)
BACKGROUND:The endovascular treatment of middle cerebral artery (MCA) aneurysms with unfavorable anatomy (wide neck, unfavorable morphology) is frequently challenging. Flow disruption with the WEB is a potentially interesting endovascular treatment for this type of aneurysm. OBJECTIVE:To report in a multicenter series the preliminary treatment experience of MCA aneurysms with flow disruption by the WEB. METHODS:Thirty-three patients with 34 MCA aneurysms were treated with the WEB in 5 European centers. The ability to successfully deploy the WEB, procedure- and device-related adverse events, morbidity and mortality of the treatment, and short-term angiographic follow-up results were analyzed. RESULTS:Most treated aneurysms were unruptured (85.3%) and were between 5 and 10 mm (85.3%) with a neck size ≥ 4 mm (88.2%). The treatment failed in 1 of the 34 aneurysms (2.9%) owing to a lack of appropriate device size. Treatment was performed exclusively with the WEB in 29 of 33 aneurysms (87.9%). Additional treatment (coiling and/or stenting) was used in 4 of 33 aneurysms (12.1%). Mortality of the treatment was 0.0% and morbidity was 3.1% (intraoperative rupture with modified Rankin Scale score of 3 at the 1-month follow-up). In short-term follow-up (range, 2-12 months), adequate occlusion (total occlusion or neck remnant) was observed in 83.3% of aneurysms. CONCLUSION:WEB flow disruption seems to be a promising technique for the treatment of complex MCA aneurysms, particularly those with a wide neck or unfavorable dome-to-neck ratio. ABBREVIATIONS:ATENA, Analysis of Treatment by Endovascular Approach of Nonruptured AneurysmsBRAT, Barrow Ruptured Aneurysm TrialCLARITY, Clinical and Anatomical Results in the Treatment of Ruptured Intracranial AneurysmsDSA, digital subtraction angiographyISAT, International Subarachnoid TrialMCA, middle cerebral arterymRS, modified Rankin Scale